2019
DOI: 10.5489/cuaj.5938
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, pilot trial of a polyethylene glycol (PEG)-coated collagen patch (Hemopatch®) for intraoperative hemostasis during deceased donor renal transplant

Abstract: Introduction: The objective of this study was to evaluate the safety and feasibility of using a polyethylene glycol (PEG)-coated collagen patch (Hemopatch®) in patients undergoing deceased donor renal transplant. The primary outcome was the amount of intraoperative estimated blood loss in those patients receiving the patch compared to without. Secondary outcomes were the subjective achievement of hemostasis, perigraft collection, and drop in hemoglobin 48 hours postoperatively. Methods: We performed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The number of SSIs in the Hemopatch® group is consistent with previously reported rates of 9–15% after ALND [20, 21]. Additionally, a number of studies on the use of Hemopatch® for a variety of indications did not show an increased risk for infections [22, 23]. Another study on the use of Hemopatch® as a dural sealant reported an SSI rate of 4.5% compared to 1.0–5.6% after dural closure without Hemopatch® [24].…”
Section: Discussionsupporting
confidence: 88%
“…The number of SSIs in the Hemopatch® group is consistent with previously reported rates of 9–15% after ALND [20, 21]. Additionally, a number of studies on the use of Hemopatch® for a variety of indications did not show an increased risk for infections [22, 23]. Another study on the use of Hemopatch® as a dural sealant reported an SSI rate of 4.5% compared to 1.0–5.6% after dural closure without Hemopatch® [24].…”
Section: Discussionsupporting
confidence: 88%
“…Based on current clinical experience, PEG hydrogel is a safe and feasible option to aid hemostasis during surgery, and hemostasis has been successfully achieved in deceased donor kidney transplantation with the assistance of PEG hydrogel. [ 59 ] The other most commonly used synthetic hydrogel called coseal is currently used as a sealant around suture sites which consists of a four‐armed PEG succinimide‐activated ester and a four‐armed PEG thiol. However, since the thiol groups on the structure of the coseal sealant are easily oxidized, special handling is required for use, which greatly increases the cost of use.…”
Section: Polymeric Micelles For Synthesis Of Responsive Hydrogels In ...mentioning
confidence: 99%
“…The use of this PEG-coated patch for hemostasis has been described across a number of surgical disciplines for both open and laparoscopic procedures. 7,8 One area of concern in laparoscopy is unintentionally activating the PEG-layer on adjacent tissue or blood while positioning the patch, which may complicate the ease of use of this patch in laparoscopy compared to open surgery. 9 Here-in, we describe our initial experience with using a PEG-coated patch in leu of traditional renorrhaphy during MIPN.…”
Section: Introductionmentioning
confidence: 99%